1995
DOI: 10.22358/jafs/69797/1995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementary feeding on the gastrointestinal strongylid eggs shedding in grazing pregnant Merino ewes

Abstract: Sixty Merino ewes during 140 days of pregnancy were naturally infected by strongylids at grazing, but 30 animals were provided a barley supplement furthermore (400 grams per head day" 1 ). Faecal samples were collected every 20 days for analysis and by means of faecal cultures the genera of strongylids present were identified. Body weight and body condition scores were also recorded every 10 days. Results showed that liveweight and body condition scores were higher in supplemented group than unsupplemented one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Helminthiasis is a chief cause of monetary losses in ruminants worldwide (Ferre et al, 1995). GI helminths are considered as one of the utmost significant and underrated problems, which hinder sheep productivity (Perry and Randolph, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Helminthiasis is a chief cause of monetary losses in ruminants worldwide (Ferre et al, 1995). GI helminths are considered as one of the utmost significant and underrated problems, which hinder sheep productivity (Perry and Randolph, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In ruminants, manipulation of host protein nutrition indeed helped hosts to regulate worm population, that is to decrease worm number, size and fecundity (Coop and Holmes, 1996;Athanasiadou et al, 2008). It has also been shown that supplementation with barley tended to reduce nematode egg excretion in grazing sheep (Ferre et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In ruminants, manipulation of host protein nutrition indeed helped hosts to regulate worm population, that is to decrease worm number, size and fecundity (Coop and Holmes, 1996;Athanasiadou et al, 2008). It has also been shown that supplementation with barley tended to reduce nematode egg excretion in grazing sheep (Ferre et al, 1995).The objective of this 4-month study was to test the hypothesis that, under unlimited grass growth, it is possible to feed lactating mares with grazed herbage only without affecting performance of mares and foals. We therefore compared performance and daily intake of energy-supplemented (with barley) and non-supplemented mares grazing together a permanent pasture.…”
mentioning
confidence: 99%